Synthesis of Spiroindolenines via Regioselective Gold(I)‐Catalyzed Cyclizations of N‐Propargyl Tryptamines. Issue 22 (29th September 2017) - Magné, Valentin; Marinetti, Angela; Gandon, Vincent; Voituriez, Arnaud; Guinchard, Xavier
Abstract: N ‐Propargyl tryptamines bearing N ‐substituents such as propargyl, allyl, alkyl or benzyl groups undergo regioselective gold‐catalyzed cyclizations to the corresponding spiroindolenines, while it was previously shown that N ‐sulfonyl‐ N ‐propargyl tryptamines lead to achiral azepino[4, 5‐ b ]indoles. An asymmetric approach to these spiroindolenines is disclosed using chiral gold complexes, leading to enantiomeric ratios up to 84/16. The spiroindolenines could be late‐stage functionalized using Huisgen cyclizations, palladium‐catalyzed cross couplings or reductions. Computational studies show that the reaction evolves via different mechanistic pathways depending on the nature of the substituent at the amine. Abstract :